Charlotte's web : a guide for the novel by E.B. White - Housel, Debra J.; White, E. B. (Huntington Beach Shell Education, 2017)
Young readers will be intrigued and eager to analyze this timeless classic by completing fun, challenging activities and lessons provided in this instructional guide for literature. This guide is the perfect tool to aid students in analyzing and comprehending this charming story. Appealing and challenging cross-curricular lessons and activities incorporate research-based literacy skills to help students become thorough readers. These lessons and activities work in conjunction with the text to teach students how to analyze and comprehend story elements in multiple ways, practice close reading and text-based vocabulary, determine meaning through text-dependent questions, and much more